Chiral bisoxazoline ligands designed to stabilize bimetallic complexes - Das, Deepankar; Mal, Rudrajit; Mittal, Nisha; Zhu, Zhengbo; Emge, Thomas J.; Seidel, Daniel (Beilstein Journal of Organic Chemistry, 2018)
Chiral bisoxazoline ligands containing naphthyridine, pyridazine, pyrazole, and phenol bridging units were prepared and shown to form bimetallic complexes with various metal salts. X-ray crystal structures of bis-nickel naphthyridine-bridged, bis-zinc pyridazine-bridged, and bis-nickel as well as bis-palladium pyrazole-bridged complexes were obtained.
Keywords: bimetallic complexes; bisoxazolines; chiral ligands; heterocycles

(untitled) - Johnson, J. S.; Evans, D. A. (Acc. Chem. Res., 2000)

(untitled) - McManus, H. A.; Guiry, P. J. (Chem. Rev., 2004)

(untitled) - Desimoni, G.; Faita, G.; Jorgensen, K. A. (Chem. Rev., 2006)

(untitled) - Vaugeois, J.; Simard, M.; Wuest, J. D. (Coord. Chem. Rev., 1995)

(untitled) - Gavrilova, A. L.; Bosnich, B. (Chem. Rev., 2004)

Multimetallic Catalysts in Organic Synthesis - Shibasaki, M.; Yamamoto, Y. (Wiley-VCH, 2004)

(untitled) - Mitić, N.; Smith, S. J.; Neves, A.; Guddat, L. W.; Gahan, L. R.; Schenk, G. (Chem. Rev., 2006)

(untitled) - Karplus, P. A.; Pearson, M. A.; Hausinger, R. P. (Acc. Chem. Res., 1997)

(untitled) - Stenkamp, R. E. (Chem. Rev., 1994)

(untitled) - Whittington, D. A.; Lippard, S. J. (J. Am. Chem. Soc., 2001)

(untitled) - Logan, D. T.; Su, X.-D.; Åberg, A.; Regnström, K.; Hajdu, J.; Eklund, H.; Nordlund, P. (Structure, 1996)

(untitled) - Gerdemann, C.; Eicken, C.; Krebs, B. (Acc. Chem. Res., 2002)

(untitled) - Kanyo, Z. F.; Scolnick, L. R.; Ash, D. E.; Christianson, D. W. (Nature, 1996)

(untitled) - Shibasaki, M.; Sasai, H.; Arai, T. (Angew. Chem., Int. Ed. Engl., 1997)

(untitled) - Shibasaki, M.; Kanai, M.; Matsunaga, S.; Kumagai, N. (Acc. Chem. Res., 2009)

(untitled) - Konsler, R. G.; Karl, J.; Jacobsen, E. N. (J. Am. Chem. Soc., 1998)

(untitled) - Trost, B. M.; Ito, H. (J. Am. Chem. Soc., 2000)

(untitled) - Trost, B. M.; Bartlett, M. J. (Acc. Chem. Res., 2015)

(untitled) - Gao, J.; Reibenspies, J. H.; Martell, A. E. (Angew. Chem., Int. Ed., 2003)

(untitled) - Gao, J.; Zingaro, R. A.; Reibenspies, J. H.; Martell, A. E. (Org. Lett., 2004)

(untitled) - Ooi, T.; Saito, A.; Maruoka, K. (Tetrahedron Lett., 1998)

(untitled) - Keiji, M. (Bull. Chem. Soc. Jpn., 2009)

(untitled) - Sharma, V.; Simard, M.; Wuest, J. D. (J. Am. Chem. Soc., 1992)

(untitled) - Vaugeois, J.; Wuest, J. D. (J. Am. Chem. Soc., 1998)

(untitled) - Wuest, J. D. (Acc. Chem. Res., 1999)

(untitled) - Constable, E. C.; Zhang, G.; Housecroft, C. E.; Neuburger, M.; Schaffner, S.; Woggon, W.-D. (New J. Chem., 2009)

(untitled) - Tschinkl, M.; Schier, A.; Riede, J.; Gabbai, F. P. (Organometallics, 1999)

(untitled) - Guo, Q.-X.; Wu, Z.-J.; Luo, Z.-B.; Liu, Q.-Z.; Ye, J.-L.; Luo, S.-W.; Cun, L.-F.; Gong, L.-Z. (J. Am. Chem. Soc., 2007)

(untitled) - Park, J.; Lang, K.; Abboud, K. A.; Hong, S. (J. Am. Chem. Soc., 2008)

(untitled) - Li, W.; Thakur, S. S.; Chen, S.-W.; Shin, C.-K.; Kawthekar, R. B.; Kim, G.-J. (Tetrahedron Lett., 2006)

(untitled) - Kawthekar, R. B.; Kim, G.-J. (Helv. Chim. Acta, 2008)

(untitled) - Annamalai, V.; DiMauro, E. F.; Carroll, P. J.; Kozlowski, M. C. (J. Org. Chem., 2003)

(untitled) - Prokofieva, A.; Dechert, S.; Grosse, C.; Sheldrick, G. M.; Meyer, F. (Chem. – Eur. J., 2009)

(untitled) - Oh, T.; Lopez, P.; Reilly, M. (Eur. J. Org. Chem., 2000)

(untitled) - Reilly, M.; Oh, T. (Tetrahedron Lett., 1995)

(untitled) - Jammi, S.; Saha, P.; Sanyashi, S.; Sakthivel, S.; Punniyamurthy, T. (Tetrahedron, 2008)

(untitled) - Keller, F.; Rippert, A. J. (Helv. Chim. Acta, 1999)

(untitled) - Takizawa, S.; Katayama, T.; Sasai, H. (Chem. Commun., 2008)

(untitled) - Takizawa, S.; Katayama, T.; Somei, H.; Asano, Y.; Yoshida, T.; Kameyama, C.; Rajesh, D.; Onitsuka, K.; Suzuki, T.; Mikami, M.; Yamataka, H.; Jayaprakash, D.; et al. (Tetrahedron, 2008)

(untitled) - Saito, A.; Yanai, H.; Taguchi, T. (Tetrahedron Lett., 2004)

(untitled) - Saito, A.; Ito, H.; Taguchi, T. (Org. Lett., 2002)

(untitled) - Kleinbeck, F.; Toste, F. D. (J. Am. Chem. Soc., 2009)

(untitled) - Zhao, D.; Yuan, Y.; Chan, A. S. C.; Wang, R. (Chem. – Eur. J., 2009)

(untitled) - Sun, J.; Yang, M.; Yuan, F.; Jia, X.; Yang, X.; Pan, Y.; Zhu, C. (Adv. Synth. Catal., 2009)

(untitled) - Sun, J.; Yuan, F.; Yang, M.; Pan, Y.; Zhu, C. (Tetrahedron Lett., 2009)

(untitled) - Sakaguchi, S.; Yoo, K. S.; O'Neil, J.; Lee, J. H.; Stewart, T.; Jung, K. W. (Angew. Chem., Int. Ed., 2008)

(untitled) - Ma, J.-A.; Cahard, D. (Angew. Chem., Int. Ed., 2004)

(untitled) - Park, J.; Hong, S. (Chem. Soc. Rev., 2012)

(untitled) - Fahrni, C. J.; Pfaltz, A. (Helv. Chim. Acta, 1998)

(untitled) - Fahrni, C. J.; Pfaltz, A.; Neuburger, M.; Zehnder, M. (Helv. Chim. Acta, 1998)

(untitled) - Tsukada, N.; Sato, T.; Mori, H.; Sugawara, S.; Kabuto, C.; Miyano, S.; Inoue, Y. (J. Organomet. Chem., 2001)

(untitled) - Seitz, M.; Kaiser, A.; Tereshchenko, A.; Geiger, C.; Uematsu, Y.; Reiser, O. (Tetrahedron, 2006)

(untitled) - Mal, R.; Mittal, N.; Emge, T. J.; Seidel, D. (Chem. Commun., 2009)

(untitled) - Nano, A.; Brelot, L.; Rogez, G.; Maisse-François, A.; Bellemin-Laponnaz, S. (Inorg. Chim. Acta, 2011)

(untitled) - Doherty, S.; Knight, J. G.; McRae, A.; Harrington, R. W.; Clegg, W. (Eur. J. Org. Chem., 2008)

(untitled) - Allen, F. H. (Acta Crystallogr., Sect. B: Struct. Sci., 2002)

(untitled) - Groom, C. R.; Bruno, I. J.; Lightfoot, M. P.; Ward, S. C. (Acta Crystallogr., Sect. B: Struct. Sci., Cryst. Eng. Mater., 2016)

(untitled) - Wolińska, E. (Tetrahedron: Asymmetry, 2014)

WO Pat. Appl. - Bessard, Y.; Crettaz, R.; Brieden, W. (Method of producing pyridazine-3,6-dicarboxylic esters, 2001)